Increasing temperature may shift availability of euphausiid prey in the Southern Ocean - Richerson, Kate; Driscoll, Ryan; Mangel, Marc (Marine Ecology Progress Series, 2018)
Climate change is predicted to affect Southern Ocean biota in complex ways. Euphausiids play a crucial role in the trophodynamics of the ecosystem, and their status under future environmental scenarios is the subject of much concern. Thysanoessa macrura is the most widely distributed, numerically abundant, and ubiquitous euphausiid south of the Polar Front and may be an underappreciated prey species. T. macrura is eurythermic and may be better able to tolerate warming ocean temperatures in comparison to the more stenothermic Antarctic krill Euphausia superba. We use temperature-dependent growth models and biomass per recruit to investigate how the availability of this euphausiid to predators may change under a range of temperature scenarios. We contrast this with the availability of E. superba and find that, under some ranges of temperature change, increasing T. macrura growth may be able to partially compensate for decreasing E. superba growth in terms of biomass available for predators. However, in spite of its considerable biomass, other aspects of this species, such as its size and habitat, may limit its potential to replace E. superba in the diet of many predators. KEYWORDS: Thysanoessa macrura · Euphausia superba · Growth · Temperature · Climate change · Krill predators · Southern Ocean · Euphausiids · Modeling
Keywords: Sørishavet; biomasse; havoppvarming; klimaendringer; krill; marin biologi; marine økosystemer; miljøendringer; plankton